Evaluation of the thermal environment in architecture hotel of Fernand Pouillon. Case of the Ziban Hotel in Biskra - Zineddine, Sara; Belakehal, Azeddine; Bennadji, Amar (Journal of Applied Engineering Science & Technology; Vol 4 No 2 (2018): Issue In Progress, 2018)
The main objective of this study is to evaluate the impact of the orientation on the thermal environment in the works of Fernand Pouillon and its role in the reduction of the strong continuous and daily variations of the temperatures. In the region of Biskra, Fernand Pouillon, seems to show his mastery of the parameters related to the external physical environment in order to create suitable indoor thermal environments in a hot and arid climate. In this regard, we used the experimental method, through the ECOTECT digital simulation program, to study the quantitative aspects of these thermal environments. Thus, we have particularly studied the influence of the orientation with respect to the sun and the wind on the thermal environments of our case study. Finally, a comparison between the temperatures, in the successive sequences, allowed us to demonstrate that the preferred choices in orientation by Fernand Pouillon are adequate or not.